2011
DOI: 10.3944/aott.2011.2283
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy in patients with diabetic foot

Abstract: VAC therapy, together with debridement and appropriate antibiotic therapy, enables a higher rate of limb salvage, especially in Wagner Grade 3 and Grade 4 ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…NPT is a non-invasive method with partially understood mechanisms of action [30], which is based on the exertion on the wound of a sub-atmospheric negative pressure within the range of -50 mmHg and -175 mmHg, via polyurethane or polyvinyl alcohol sponge, fixed to the wound by an adhesive foil that provides a waterproof environment. The pressure and suction effect are provided by a digitally controlled pump, connected to the sponge by a flexible tube, and the exudates are collected in a receivertank with a capacity of 500 mL or 1000 mL [31]. NPT acts on interstitial fluid excess, thus reducing edema, improving tissue perfusion and removing infectious factors.…”
Section: Resultsmentioning
confidence: 99%
“…NPT is a non-invasive method with partially understood mechanisms of action [30], which is based on the exertion on the wound of a sub-atmospheric negative pressure within the range of -50 mmHg and -175 mmHg, via polyurethane or polyvinyl alcohol sponge, fixed to the wound by an adhesive foil that provides a waterproof environment. The pressure and suction effect are provided by a digitally controlled pump, connected to the sponge by a flexible tube, and the exudates are collected in a receivertank with a capacity of 500 mL or 1000 mL [31]. NPT acts on interstitial fluid excess, thus reducing edema, improving tissue perfusion and removing infectious factors.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the patients was 58.2 years in VAC group and 57.2 years in conventional dressing group. In a similar study evaluating the effect of negative pressure wound therapy in patients with diabetic foot, there were 15 patients treated with VAC; ten men and five women, [17]. In another study, measuring the influence of the application of platelet-enriched plasma in oral mucosal wound healing ten patients were included in the study, five males and five females, with a mean age of 54.2+/−9.1 years for females and 57.6+/−6.9 years for males [18].…”
Section: Discussionmentioning
confidence: 99%
“…Nather et al reported a 100% limb salvage in 11 patients with diabetic foot ulcers treated with VAC therapy, presenting Wagner grade 2 or 3 wounds with an average length of stay of 23·3 days. Ulusal et al reported an amputation rate of 37% , with an average hospitalisation of 32 days. The reason for this higher amputation rates in comparison to those in the literature is that 80% of the subjects had Wagner Grade 3 and 4 wounds.…”
Section: Discussionmentioning
confidence: 99%